A numerical simulation of vehicle dynamics behavior for a four-wheel steering vehicle with the passive control system - Maoqi, Li; Ishak, M. I.; Peeie, M. H. (Faculty Mechanical Engineering, UMP, 2022)
The Advanced Driver Assistance System (ADAS) is a technology in the vehicle to assist drivers in mitigating road risk and improving maneuverability. The system is capable of providing warnings to drivers and even executing an action if necessary. However, these systems are limited to the sensors and capability of the vehicle. Increasing the degree of freedom of a vehicle could potentially develop new ADAS with more efficiency. Along with the X-By-Wire technology, a four-wheel drive and independent steering (4WDIS) can be produced as a part of ADAS, especially for electric vehicles. In this research, an understanding of the steering characteristic of a 4WDIS during steady-state cornering (SSC) is presented using numerical simulation in MATLAB. An actual Segment B type vehicle is used as a simulation model and a preliminary two-wheel steering SSC simulation was performed to determine the steering characteristics. The model is modified to include a rear steer angle with a passive control system and the SSC simulation was repeated. The results show that the vehicle can perform SSC by increasing the yaw rate at high speed using the opposite steering mode. Meanwhile, parallel steering mode is suitable during low-speed cornering which can increase the yaw rate while maintaining stability.